Effects of the lncRNA MALAT1 gene region rs664589 site mutation on acute myocardial infarction in Chinese Han: Impact of rs664589 mutation on AMI in Chinese Han - Yu, Huamin; Tu, Sijia; Shen, Chaofeng; Bai, Xinghua; Sun, Jindong; Shi, Mingjuan; Li, Cairong; Yuan, Hong (Cellular and Molecular Biology, 2024)
We aimed to study the association between the non-coding region of the lncRNA MALAT1 gene, the non-coding region rs664589 C>G variant, and the risk of acute myocardial infarction (AMI) in the Chinese Han population. 165 NSTEMI and 135 STEMI patients were enrolled in the study. An additional 150 healthy individuals were enrolled as the controls. All subjects were analyzed for the MALAT1 rs664589 locus genotype. The receiver operating curve (ROC) was used to determine the effect of MALAT1 rs664589 single nucleotide polymorphism (SNP) on the diagnosis of AMI by plasma lncRNA MALAT1. The MALAT1 rs664589 site G allele carrier was 1.39 times more likely to have NSTEMI than the C allele carrier (95% CI: 1.16-1.61, P = 0.001) and 1.59 times more likely to have STEMI than the C allele carrier (95% CI: 1.31-1.85, P < 0.001). The MALAT1 rs664589 site C>G mutation resulted in an increase in the area under the ROC curve (AUC) of the plasma lncRNA MALAT1 level for the diagnosis of AMI. The plasma lncRNA MALAT1 levels in AMI patients were negatively correlated with hsa-miR-1972, hsa-miR-194-5p, hsa-miR-4717-5p, hsa-miR-6735-3p, and hsa-miR-3677-5p (r = -0.81, -0.75, -0.66, -0.71, and -0.88). The C>G mutation of MAL6641 rs664589 causes an increased risk of AMI in the Chinese Han population. The SNP at this site affects the value of plasma lncRNA MALAT1 in the diagnosis of AMI. The specific mechanism may indicate that the C>G mutation of the MALAT1 rs664589 changes the regulation of miRNAs expression by lncRNA MALAT1.